Description of Ascidia paulayi sp. nov. (Phlebobranchia: Ascidiidae) from French Polynesia, with a discussion about the Ascidia sydneiensis Stimpson, 1855 group - Bonnet, Nadia Yk; Lotufo, Tito Mc (Zootaxa, 2015)
In the last decade, new surveys were made in French Polynesia as part of the Moorea Biocode project to improve the knowledge about the regional fauna. Here we describe Ascidia paulayi sp. nov., a new species of Ascidiidae. Due its similarity with A. sydneiensis, a discussion about the species of this group complements the study.